2021
DOI: 10.3390/nano11041059
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Rapid Photocatalytic Degradation of Methyl Orange Dye Using Al/ZnO Nanoparticles

Abstract: ZnO and Aluminum doped ZnO nanoparticles (Al/ZnO NPs) were successfully synthesized by the sol-gel method. Together with the effect of calcination temperatures (200, 300 and 400 °C) and Al dosage (1%, 3%, 5% and 10%) on structural, morphological and optical properties of Al/ZnO NPs, their photocatalytic degradation of methyl orange (MO) dye was investigated. The calcination temperatures at 200, 300 and 400 °C in forming structure of ZnO NPs led to spherical nanoparticle, nanorod and nanoflake structures with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…Semiconductor photocatalysts, such as anatase TiO 2 , have played an important role in providing the solution due to their important optical and electronic properties that make them an excellent candidates in different applications such as solar fuel production, CO 2 reduction, pollution degradation, and hydrogen production [1][2][3][4][5]. Despite the large number of studies on TiO 2, there remains a big challenge related to its wide band gap that forbids the absorbance of light in the visible range and consequently reduces its photocatalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor photocatalysts, such as anatase TiO 2 , have played an important role in providing the solution due to their important optical and electronic properties that make them an excellent candidates in different applications such as solar fuel production, CO 2 reduction, pollution degradation, and hydrogen production [1][2][3][4][5]. Despite the large number of studies on TiO 2, there remains a big challenge related to its wide band gap that forbids the absorbance of light in the visible range and consequently reduces its photocatalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Piangjai Peerakiatkhajohn et al [ 40 ] used the sol-gel method to prepare low calcination temperature zinc oxide nanosheets and visible light-responsive Al-doped zinc oxide nanosheets. The results showed that calcination temperature and al doping had significant effects on the morphology, absorption properties and photocatalytic activity of zinc oxide nanoparticles.…”
Section: Zinc Oxide Doped With Transition Metal Ionsmentioning
confidence: 99%
“…To avoid moisture, it was filtered and cleaned multiple times with distilled water before being dried in a hot air oven at 90 • C for 5 h. Consequently, the FLG/MOs nanocomposites were calcined in a muffle furnace. Those temperatures were FLG/CeO 2 at 600 • C for 4 h [17], FLG/CuO at 600 • C for 4 h [18], FLG/SnO 2 at 600 • C for 4 h [19], FLG/CdO at 400 • C for 4 h [20], FLG/ZnO at 400 • C for 12 h [21], and FLG/TiO 2 at 400 • C for 2 h [22]. For comparison, pure metal oxide (MOs; CeO 2 , CuO, SnO 2 , CdO, ZnO, and TiO 2 ) NPs were also produced by the same technique without GO and followed by different calcination temperatures.…”
Section: Synthesis Of Flg/metal Oxide Nanocompositesmentioning
confidence: 99%